x+18+4x=-11-4x-16

Simple and best practice solution for x+18+4x=-11-4x-16 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for x+18+4x=-11-4x-16 equation:


Simplifying
x + 18 + 4x = -11 + -4x + -16

Reorder the terms:
18 + x + 4x = -11 + -4x + -16

Combine like terms: x + 4x = 5x
18 + 5x = -11 + -4x + -16

Reorder the terms:
18 + 5x = -11 + -16 + -4x

Combine like terms: -11 + -16 = -27
18 + 5x = -27 + -4x

Solving
18 + 5x = -27 + -4x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '4x' to each side of the equation.
18 + 5x + 4x = -27 + -4x + 4x

Combine like terms: 5x + 4x = 9x
18 + 9x = -27 + -4x + 4x

Combine like terms: -4x + 4x = 0
18 + 9x = -27 + 0
18 + 9x = -27

Add '-18' to each side of the equation.
18 + -18 + 9x = -27 + -18

Combine like terms: 18 + -18 = 0
0 + 9x = -27 + -18
9x = -27 + -18

Combine like terms: -27 + -18 = -45
9x = -45

Divide each side by '9'.
x = -5

Simplifying
x = -5

See similar equations:

| .333x+8=x+10 | | x^2-8x-16=23 | | .5x+8=x+10 | | 3x+51= | | x^2=500 | | 43+2x=32 | | 3(3)+5(4)=29 | | 6x-43=3x-10 | | 93+4=[17-(2+3)] | | 4x-7=3.5+x | | 6x^2+15=0 | | 4Y^2+3Y-10=0 | | -18x-30=6 | | 3x+5y=29 | | 82-4x=23x+16 | | 12-7x=111-28x | | -6c+9=-4c-3 | | 6x+5=-79-8x | | 6x^2+37x-35=0 | | -2x=7x-18 | | 2x^2+15=0 | | 4(2c-3)-3(c-4)= | | 80Y^2-210Y-245=0 | | y=-2.5x+4 | | 8=z-5 | | 6x+15=21 | | 3z-14=-13 | | 3x^2-16x-1=0 | | 9(y-4)+5(y+2)=16 | | 3x+7+38=180 | | n+10-2n=-5(n+2) | | w-10=8 |

Equations solver categories